2021
DOI: 10.1111/1471-0528.17033
|View full text |Cite
|
Sign up to set email alerts
|

Early medical abortion by telemedicine in the United Kingdom: a costing analysis

Abstract: Objective To determine the potential cost savings resulting from the introduction of routine early medical abortion (EMA) at home by telemedicine in the UK.Design A costing study.Setting The UK.Population Women in 2020 undergoing EMA provided by three independent abortion providers and two National Health Service (NHS) abortion clinics.Methods Computation of the costs of each abortion procedure and of managing failed or incomplete abortion and haemorrhage requiring blood transfusion. Main outcome measures Cost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…(1,17) The concomitant acceleration in trend toward more EMAs also has cost implications: EMA is less expensive to provide than surgical abortion, and earlier abortions are associated with a reduction in the need for costly surgical management of complications such as incomplete abortion and continuing pregnancy. (18) NICE estimates that in England a reduction of one day in gestational age at abortion could save £1.6 million per year – our findings that the approval of home use of misoprostol facilitated abortions happening over three days earlier show a significant economic potential of the change. (1,27)…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…(1,17) The concomitant acceleration in trend toward more EMAs also has cost implications: EMA is less expensive to provide than surgical abortion, and earlier abortions are associated with a reduction in the need for costly surgical management of complications such as incomplete abortion and continuing pregnancy. (18) NICE estimates that in England a reduction of one day in gestational age at abortion could save £1.6 million per year – our findings that the approval of home use of misoprostol facilitated abortions happening over three days earlier show a significant economic potential of the change. (1,27)…”
Section: Discussionmentioning
confidence: 74%
“…There is also strong evidence that earlier abortions are more cost-effective for health systems: the savings a consequence of choosing medical over surgical abortions and preventing complications. (1,17,18) In December 2018, the Secretary of State for Health in England approved "home" as a place where misoprostol as part of medical abortion regimen could lawfully be administered. This measure, conforming with the World Health Organization (WHO) guidelines, (19) brought England in line with Wales, where home use had been approved in June 2018, and with Scotland, where it was approved in October 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has also shown it to be safe (19) and cost-effective, resulting in significant cost savings for the NHS. (20) This model of care of aligns with broader trends within 21st century health systems: recognition of the need for patient-centred approaches, shared decision making in health care, and supported self-management, principles supported by advances in digital technology. (21) The strong plea from women in our study for choice must be heeded.…”
Section: Contextualisation and Interpretationmentioning
confidence: 99%
“…Research among providers suggests they consider the new model more patient centred 15. An economic evaluation estimates that the telemedicine model saved the NHS at least £3m (€3.6m; $4m) a year 16…”
mentioning
confidence: 99%